PENGARUH LABA BERSIH TERHADAP DIVIDEN SERTA DAMPAKNYA PADA HARGA SAHAM PERUSAHAAN SEKTOR AGRIKULTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ahmad Mudzakir (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
This study aims to determine how the effect of net income on stock prices directly and indirectly through the dividend variable in companies listed on the Indonesia Stock Exchange. The population in this study were companies listed on the Indonesia Stock Exchange for the period 2013 to 2018. After selecting the population according to the purposive sampling method, there were 5 companies in the agricultural sector used as samples. This research is an associative study with a quantitative approach. The study used a path analysis model using linear regression analysis techniques by first doing classic assumption tests such as normality test, heterocedasticity, multicollinearity and autocorrelation. The results showed that net income has a positive and significant effect on dividends, dividends have a positive but not significant effect on stock prices, net income has a positive and significant effect on stock prices, the direct effect of net income on stock prices is 0.613, the indirect effect of net income on prices shares through dividends of 0.224 and the effect of total net income on stock prices of 0.837.Keywords: net income, dividends, stock prices and path analysis